International/Cooperative Frameworks for Remedying the Safety Issues Present in Immigration Management - Nagyné Csobolyó, Eszter (Magyar Rendészet, 2018)
Today we can declare, that the question of migration and safety/security belong together. The creation and/or upkeep of safety is a public duty, on which civil and law enforcement, national and international agencies need to take action, working together as a group. The aim of this article is to show the international cooperation.